Reverse shoulder arthroplasty for the treatment of nonunions of the surgical neck of the proximal part of the humerus (type-3 fracture sequelae) - Raiss, Patric; Bruckner, Thomas; Loew, Markus (The journal of bone & joint surgery. A, American volume, 2014)
Background: Fracture sequelae of the proximal part of the humerus are challenging conditions, and various treatment options have been described. The purpose of this multicenter study was to analyze the clinical and radiographic outcomes as well as the complications following semiconstrained reverse total shoulder arthroplasty for the treatment of nonunion of a surgical neck fracture of the proximal part of the humerus. Methods: Thirty-two patients with a mean age of sixty-eight years (range, forty-eight to eighty-three years) managed with a reverse shoulder arthroplasty for the treatment of nonunion of a proximal humeral fracture were analyzed clinically and radiographically. The mean duration of follow-up was four years (range, two to twelve years). The Constant score, active shoulder mobility, all complications, and revision procedures were recorded. Results: The mean Constant score increased from 14.2 points (range, 2 to 35 points) to 46.6 points (range, 6 to 75 points) (p < 0.001). The mean shoulder flexion increased from 42.9° (range, 0° to 160°) to 109.7° (range, 0° to 170°) (p < 0.001), and the mean external rotation increased from 0.5° (range, −40° to 60°) to 13.1° (range, −30° to 60°) (p < 0.005). No component loosening occurred, but 50% (sixteen) of the patients had radiographic evidence of scapular notching. There were thirteen complications (41%) leading to nine revision surgical procedures (28%). The most common complication was a dislocation following reverse shoulder arthroplasty, which occurred in 34% (eleven) of the patients. An intraoperative resection of the humeral head fragment and the tuberosities was associated with increased risk of dislocation (p < 0.007). Conclusions: Nonunions of the proximal part of the humerus can be treated with reverse shoulder arthroplasty. Although clinical outcomes improved significantly, we found an unacceptably high rate of dislocations associated with intraoperative resection of the tuberosities. The tuberosities and the attached rotator cuff should be preserved if possible to reduce the risk of dislocation after reverse total shoulder arthroplasty. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.